Kinetic Study on Flooded Soil Recovery Using Soil Containing Arbuscular Mycorrhizal Fungi - N., Zainol; Nanthienie, Thangaperumal; N. H., Aziz (EDP Sciences, 2015, 2016)
The purpose of this research was to determine the kinetic parameters for flooded soil recovery via soil containing Arbuscular Mycorrhizal fungi (AMF). The general procedures of this experiment started by preparation of simulated flooded soil (FS) and soil containing AMF (SA). Mixed soil was prepared by mixing FS and SA with ratio 1:1. Onion plant was chosen as a host plant and planted in the mixed soil for 14 days. The plantation was conducted in ambient temperature. The nutrients (nitrogen, phosphorus and potassium) concentrations in the soil were tested using HACH Spectrophotomer. The Michaelis-Menten equation was used to study the nutrients recovery in soil. The Lineweaver-Bulk plot was used to solve the Michaelis-Menten equation. From the experiment conducted, the maximum nutrient uptake (Vmax) and bonding affinity (Km) obtained for nitrogen (N) were 6.28mg/l.d and 82.17 mg/l, for phosphorus (P) were 9.80 mg/l.d and 60.96 mg/l.d and for potassium (K) were 0.07mg/l.d and 4.55mg/l. By comparing the result with other researcher, it showed that the Vmax and Km of nitrogen (N) and phosphorus (P) obtained were higher than other research. This was because the onion required a high level of N and P in the soil compared to other host plant.